Drug Seeking and Relapse: New Evidence of a Role for Orexin and Dynorphin Co-transmission in the Paraventricular Nucleus of the Thalamus - Alessandra Matzeu; Rémi Martin-Fardon (Frontiers in Neurology, 2018)
The long-lasting vulnerability to relapse remains the main challenge for the successful treatment of drug addiction. Neural systems that are involved in processing natural rewards and drugs of abuse overlap. However, neuroplasticity that is caused by drug exposure may be responsible for maladaptive, compulsive, and addictive behavior. The orexin (Orx) system participates in regulating numerous physiological processes, including energy metabolism, arousal, and feeding, and is recruited by drugs of abuse. The Orx system is differentially recruited by drugs and natural rewards. Specifically, we found that the Orx system is more engaged by drugs than by non-drugs, such as sweetened condensed milk (SCM) or a glucose saccharin solution (GSS), in an operant model of reward seeking. Although stimuli (S+) that are conditioned to cocaine (COC), ethanol, and SCM/GSS equally elicited reinstatement, Orx receptor blockade reversed conditioned reinstatement for drugs vs. non-drugs. Moreover, the hypothalamic recruitment of Orx cells was greater in rats that were tested with the COC S+ vs. SCM S+, indicating of a preferential role for the Orx system in perseverative, compulsive-like COC seeking and not behavior that is motivated by palatable food. Accumulating evidence indicates that the paraventricular nucleus of the thalamus (PVT), which receives major Orx projections, mediates drug-seeking behavior. All Orx neurons contain dynorphin (Dyn), and Orx and Dyn are co-released. In the VTA, they play opposing roles in reward and motivation. To fully understand the physiological and behavioral roles of Orx transmission in the PVT, one important consideration is that Orx neurons that project to the PVT may co-release Orx with another peptide, such as Dyn. The PVT expresses both Orx receptors and κ opioid receptors, suggesting that Orx and Dyn act in tandem when released in the PVT, in addition to the VTA. The present review discusses recent findings that suggest the maladaptive recruitment of Orx/Dyn-PVT neurotransmission by drugs of abuse vs. a highly palatable food reward.